Fear of Happiness, Flourishing, and Hope Among College Students at the University of Rizal System-Morong Rodelin A. Balisi ... et al... - Rodelin A. Balisi; Catherine Joy G. Fabro; Eljohn Jeferson L. Lianko; Dianne C. Valenzuela; Jhona Mae F. Villafania; Alfonso, Czarina Ann B. (2024)
Fear of happiness is a relatively recent concept that emphasizes an individual's fear of experiencing happiness due to its anticipated negative consequences. Research on fear of happiness as an individual construct and its relation with other variables is limited. Notably, fear of happiness is more prevalent in societies that value collectivism than individualistic ones. Due to the well-known collectivist character of the Filipino people, the researchers sought to conduct a study in a Filipino context. This study aims to understand the fear of happiness further and examine its relationship with university students' levels of hope and flourishing. A total of two hundred (200) students from the University of Rizal System-Morong participated in the study. In a cluster sampling technique, fifty (50) respondents were randomly selected from each college department: the College of Science, College of Education, College of Engineering, and College of Information Technology. For this study, a non-experimental correlational research design was employed. A quantitative method was applied to assess the statistical validity of this study. The original Fear of Happiness Scale developed by Joshanloo (2013); Flourishing Scale developed by Diener, Wirtz, Tov, Kim-Prieto, Choi, Oishi, & Biswas-Diener (2010); and the Dispositional Hope Scale developed by Snyder, Harris, Anderson, Holleran, Irving, Sigmon, & Harney (1991) were administered to gather the necessary data from the respondents. This allowed the researchers to establish and interpret the correlations between the variables of this study. The data analysis included the mean and standard deviations of the scores obtained from each questionnaire, suggesting higher levels of flourishing and hope compared to fear of happiness. Further analysis involved calculating Spearman's rho correlations. The correlation between fear of happiness and flourishing was insignificant (p = 0.073). However, the correlation between fear of happiness and hope was significant (p = 0.000) according to Spearman's rho. After analyzing the data, the null hypothesis for the relationship between fear of happiness and flourishing coil was not rejected, while it was rejected for fear of happiness and hope.
Thesis